1985
DOI: 10.1113/jphysiol.1985.sp015750
|View full text |Cite
|
Sign up to set email alerts
|

The mechanical properties of ciliary bundles of turtle cochlear hair cells.

Abstract: SUMMARY1. The mechanical behaviour of the ciliary bundles of hair cells in the turtle cochlea was examined by deflecting them with flexible glass fibres ofknown compliance during simultaneous intracellular recording of the cell's membrane potential.2. Bundle motion was monitored through the attached fibre partially occluding a light beam incident on a photodiode array. The change in photocurrent was assumed to be proportional to bundle displacement.3. For deflexions of 1-100 nm towards the kinocilium, the stif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
315
2
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 458 publications
(334 citation statements)
references
References 32 publications
15
315
2
1
Order By: Relevance
“…This bundle does not behave as a merely passive transducer. Evoked hair-bundle oscillations instead demonstrate that the hair bundle is capable of producing active transient motions and of amplifying mechanical inputs [17][18][19][20]. Moreover, hair bundles can produce limit-cycle oscillations, a phenomenon that may underly otoacoustic emissions [21].…”
mentioning
confidence: 99%
“…This bundle does not behave as a merely passive transducer. Evoked hair-bundle oscillations instead demonstrate that the hair bundle is capable of producing active transient motions and of amplifying mechanical inputs [17][18][19][20]. Moreover, hair bundles can produce limit-cycle oscillations, a phenomenon that may underly otoacoustic emissions [21].…”
mentioning
confidence: 99%
“…Visual and video observations of hair bundle motion during slow (∼1 Hz) deflections suggested that bundles of bullfrog saccular hair cells and turtle cochlear hair cells move as a unit without splay [1,5,6,11]. Optical measurements confirmed that the bundle moves as a unit even up to high frequencies [12,14], at least for small deflections (<50 nm).…”
Section: Introductionmentioning
confidence: 66%
“…Therefore, it is possible that long-term adaptation is mediated by a suppression of active amplification. To further support this hypothesis we studied the spontaneous emission of electrical noise (Crawford and Fettiplace, 1985;Martin et al, 2003) which is proposed to be a manifestation of active amplification (Martin et al, 2003). A link between active amplification and long-term adaptation predicts that activation would have the same depressing effect on test responses and on the spontaneous noise.…”
Section: Long-term Adaptation Results From Suppression Of Active Amplmentioning
confidence: 99%
“…Single mechanoreceptor cells are thought to underlie active mechanical amplification since hair cells exhibit all of the manifestations of the process, including enhanced gain of minute inputs and the production of spontaneous mechanical emissions (Jaramillo et al, 1993;Hudspeth, 1999, 2001;Martin et al, 2003). These spontaneous mechanical emissions are accompanied by an electrical component (Crawford and Fettiplace, 1985;Martin et al, 2003).…”
Section: Introductionmentioning
confidence: 99%